The Effect of Perceived Deterrence on Compliance with Authorities: The Moderating Influence of Procedural Justice - Verboon, Peter; Dijke, Marius van (International Journal of Criminology and Sociology, 2012)
In order to stimulate compliance, authorities often use deterrence instruments. However, scientific literature from the fields of criminology, sociology and psychology has not been consistent in when or why deterrence is effective in shaping compliance. In the present study we investigated the role of procedural justice in relation to deterrence. Procedural justice has strong effects on people’s attitudes and behaviour regarding the social collective, including compliance with authorities. We argued that particularly authorities who are considered procedurally fair are successful in stimulating compliance with the use of deterrence instruments. In support of these ideas, a field survey in which we focused on sanction severity as the first element of deterrence and an experiment in which we focused on detection probability as the second element of deterrence revealed that procedural justice and deterrence instruments interactively strengthen each other’s effect in promoting compliance. These finding may partly explain the sometimes-contradictory results from prior work about the effectiveness of deterrence by supporting a justice perspective on the effectiveness of deterrence in increasing compliance with authorities.